THE EFFECTIVENESS OF TRAINING IMPARTED TO THE POLICE FORCE IN THE NEWLY MERGED DISTRICT OF KHYBER, KHYBER PAKHTUNKHWA PROVINCE, PAKISTAN - Ahmad Ullah; Syed Aizaz Ali Shah (International Journal of Contemporary Issues in Social Sciences, 2024)
Training is Pivotal for the capacity building of Police investigation officers, as it enhances their service delivery and professionalism. This research endeavour aimed to assess the nature and efficiency of police training of the three Tehsils including Jamrud, Bara and Landikotal of the newly merged district of Khyber. In this regard, quantitative research was carried out by selecting 40 trained male police investigation officers from district Khyber through purposive sampling technique and data was collected through interview schedule. Research findings showed that majority of police investigation officers received practical training on the use of different types of firearms and ammunition, including Short Machine Gun (SMG), Long Machine Gun (LMG), pistol, and Anti-tank Rocket Grenade Launcher 7 (RPG7) during their training. In addition, the investigation officers who have undergone through the training also received physical training (running, strength training and drill), fingerprints taking, public disorder and riot management, interrogation skills, community oriented policing, communication skills etc. Additionally, two weeks core investigation training was provided to the investigation officers of Khyber to enable them to collect the evidence properly. The overall duration of training was three months and each batch comprises around two hundred and fifty investigation officers. Further, it was found that majority of the respondents were not satisfied from the training process, and there were some problems including accommodation as some of the police officers of Khyber were in vulnerable age group, being over 40, making it difficult for them to undergo training after many years of service as they were serving khasadar before merger in Khyber and even have not received the initial recruit course. Further, they lack proper educational credentials and faced difficulties to receive the theoretical aspect of training, and training lack modules like digital forensics and use of IT in investigation. This study recommends providing proper accommodation for police officers during training, specialized training on crime scene processing, recreational activities, and leniency in physical training for the senior officers to ensure their successful completion of training program.